Experiences, Challenges, and Teaching Strategies: Basis for Classroom Interactive Performance - Riego, Arman V.; Aldeguer, Citrobelle A. (Future Science / FSH-PH Publications, 2025)
This study explored teaching strategies employed by secondary teachers in the Division of La Carlota City for literature instruction. Utilizing Focus Group Discussions (FGDs) with seven English teachers from various schools and document analysis, the research examined engagement, exploration, and exit themes related to teaching practices. During the engagement phase, it was found that the nature of literature teaching has evolved significantly over the past 5–10 years, emphasizing the use of interactive multimedia, online platforms, and diverse text analysis approaches. Challenges such as electronic distractions and students' struggles with comprehension were highlighted. In the exploration phase, teachers expressed the fulfillment of teaching literature, fostering cultural appreciation, and collaboration among peers. Challenges were addressed through simulated reading programs, engagement with complex texts, contextualization, and transitioning from global to academic literature. Effective strategies included the use of appropriate resources, pre-selection questioning, integration of contemporary literary works, and multimedia tools. Teachers also emphasized fostering appreciation for literature, deepening understanding of literary elements, and providing time for guided exploration of complex texts. In the exit phase, critical thinking, inclusivity, comprehensive assessment strategies, and professional collaboration emerged as essential skills and practices. The study recommends implementing interactive teaching methods, integrating technology, and performance-based assessments to enhance engagement and participation in literature instruction.